2007
DOI: 10.1007/s00330-007-0706-y
|View full text |Cite
|
Sign up to set email alerts
|

Value of Micronester coils in port-catheter implantation for continuous hepatic arterial infusion chemotherapy with fixed catheter tip method

Abstract: To retrospectively evaluate the use of Micronester coils in port-catheter implantation with the fixed catheter tip method in comparison with other previously used coils. The cohort of this study was 143 consecutive patients with unresectable advanced liver cancer for whom a port-catheter system was percutaneously implanted. In the most recent 32 patients, Micronester coils were used for catheter tip fixation. Details of embolic agents for fixation, persistent blood flow beyond the distal end of the indwelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(55 reference statements)
0
2
2
Order By: Relevance
“…d The port was placed in the right region of the hypogastric area (white curved arrow). The catheter was placed in the subcutaneous tunnel (thin white arrows), making a loop from just under the inguinal ligament in the cranial direction at the superior border to center of the femoral head (thin black arrow) tip method with a coil or n-butyl cyanoacrylate-lipiodol mixture is associated with a rate of 5-6.8% [11,14,[16][17][18]. The present study found higher rates of hepatic arterial occlusion than observed for the conventional reservoir.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…d The port was placed in the right region of the hypogastric area (white curved arrow). The catheter was placed in the subcutaneous tunnel (thin white arrows), making a loop from just under the inguinal ligament in the cranial direction at the superior border to center of the femoral head (thin black arrow) tip method with a coil or n-butyl cyanoacrylate-lipiodol mixture is associated with a rate of 5-6.8% [11,14,[16][17][18]. The present study found higher rates of hepatic arterial occlusion than observed for the conventional reservoir.…”
Section: Discussioncontrasting
confidence: 69%
“…Catheter occlusion was reported in 0-11.4% of cases [5,7,8,11,[13][14][15][16][17][18][21][22][23]. One study reported a high rate of occlusion using a 5-F catheter [23]; therefore, catheter size and occlusion rate do not appear to be related.…”
Section: Discussionmentioning
confidence: 92%
“…We used a non-tapered indwelling catheter, such as a 5-Fr or 5.8-Fr polyurethane catheter, where a tip-fixation effect may be expected, and no coil insertion or n-butyl cyanoacrylate embolization was performed for additional catheter-tip fixation. In our study, catheter dislocation occurred more frequently than in previous reports using the classic fixed-catheter-tip method (18, 19, 21-25). However, among 18 of the 19 cases with complications that required correction of the implantable port-catheter system, correction was possible in the majority of cases with the distal catheter tip at the gastroepiploic or gastroduodenal artery.…”
Section: Discussioncontrasting
confidence: 61%
“…A review of large published studies describing percutaneous port-catheter system placement for hepatic arterial infusion chemotherapy using the fixed-catheter-tip method, revealed that the rate of indwelling catheter dislocation was 2-8% (16, 18, 19, 21-25), and the rate of hepatic artery obstruction was 3-20% (19, 21-25). However, several important problems exist with this method such as the difficulty in catheter removal (19), the long procedure duration for catheter-tip fixation using microcoils alone or with n-butyl cyanoacrylate, and the migration of the coil or cast of n-butyl cyanoacrylate.…”
Section: Discussionmentioning
confidence: 99%